Subcutaneos Implantable Cardioverter: Defibrillator: Is the Conventional Pre-Implant Screening Enough to Assess Eligibility? - Galizia Brito, Victoria; Falcó Martinez, Teresa; Bibiloni Cladera, Aina; Lozano Medina, Diego; Peral Disdier, Vicente; Expósito Pineda, María del Carmen; Grande Morales, Carlos (International Journal of Innovative Research in Medical Science, 2023)
Aims: The subcutaneous implantable cardioverter-defibrillator (S-ICD) requires screening prior to implantation. Surface anatomical landmarks (SAL) guide the screening. The heart silhouette shows variations, therefore, these landmarks may differ. We aimed to determine the concordance between SAL and fluoroscopy guided screening, and analyze discordance predicting factors. Methods: We performed a conventional SAL guided screening (CS) in left and right parasternal electrode position (LPP/RPP) to candidates for S-ICD. Subsequently, we performed a fluoroscopy guided screening (FGS) according to cardiac silhouette. Screenings in which at least the result of one sensing vector did not coincide were considered “discordant”. A comparison was done between discordant vs. concordant cases. A simple binary logistic regression analysis was performed to assess the risk of being discordant individually for each of the variables. Results: The results of CS and FGS were compared in 110 patients (220 comparisons: 110 LPP and 110 RPP). 90 (40.91%) were discordant in at least one sensing vector (46 in LPP and 44 in RPP). In 3 patients (2.73%) the indication of which type of defibrillator was implanted changed according to the FGS. There were no significant differences between the discordant and concordant screening patients. Conclusion: There is a level of discordance between CS and FGS. There were no analyzed factors that were able to predict discordance between these two screening methods. It might be reasonable to perform FGS before implant.